2004
DOI: 10.4028/www.scientific.net/msf.449-452.901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argon Ion Bombardment on Diffusion Bonded Joint of Various Metals

Abstract: Specimens of aluminum (Al), austenitic stainless steel (SUS304L), pure iron (Fe) and Oxygen-free high conductivity copper (Cu) were treated by argon ion bombardment, and then were bonded by diffusion bonding method. The effects of argon ion bombardment on diffusion-bonded joints of four kinds of metallic materials were compared from the tensile strength at real bonded area and the fractographs. The results showed that bonding temperature was lowered by argon ion bombardment treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has been shown that oxide films on a faying surface form inclusions at the bonding interface, and the inclusions degrade the bond. 1,2) Ion beam bombardment removes the oxide film on the faying surface, thus lowering the bonding temperature. [1][2][3] Using Ar-beam surface treatment, some joints can be made even at room temperature, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that oxide films on a faying surface form inclusions at the bonding interface, and the inclusions degrade the bond. 1,2) Ion beam bombardment removes the oxide film on the faying surface, thus lowering the bonding temperature. [1][2][3] Using Ar-beam surface treatment, some joints can be made even at room temperature, e.g.…”
Section: Introductionmentioning
confidence: 99%